Role of the venus kinase receptor in the female reproductive physiology of the desert locust, Schistocerca gregaria - Lenaerts, Cynthia (Sci Rep, 2017)
Venus kinase receptors (VKR) are a subfamily of invertebrate receptor tyrosine kinases, which have only recently been discovered. They contain an intracellular tyrosine kinase domain and an extracellular Venus FlyTrap domain. VKRs have been functionally and pharmacologically characterized in only two invertebrate species, namely the human parasite Schistosoma mansoni and the mosquito Aedes aegypti, where they play a crucial role in oogenesis. Here, we report the characterization of a VKR in the desert locust, Schistocerca gregaria. We performed an in-depth profiling study of the SgVKR transcript levels in different tissues throughout the female adult stage. Using the RNA interference technique, the possible role of SgVKR was investigated. SgVKR knockdown had significant effects on ovarian ecdysteroid levels and on the size of oocytes during the vitellogenic stage. SgVKR is probably involved in the complex cross-talk between several important pathways regulating female reproductive physiology. Contrary to A. aegypti and S. mansoni, we cannot conclude that this receptor is essential for reproduction, since silencing SgVKR did not affect fecundity or fertility. Considering the evolutionary distance between A. aegypti and S. gregaria, as well as the differences in regulation of their female reproductive physiology, this article constitutes a valuable asset in better understanding VKRs.